Treatment of black liquor by the anaerobic upflow filter - Manalastas, Susan Mascarinas
This study resulted from an experimental investigation made to verify the effectiveness of anaerobic treatment of black liquor. The anaerobic filter of the upflow type was used as the treatment process. The anaerobic filter had been found to be effective with the black liquor in terms of gas recovery, but low in treatment efficiency. Results showed that using a hydraulic loading of 700 ml per day, BOD reduction was 9.1 percent and gas production rate was 750 ml per day; for 1,000 ml per day hydraulic loading, BOD reduction was 9.5 percent and the rate of gas production was 1,174 ml per day at 1,200 ml per day loading gave a 19.3 percent BOD reduction and a gas production rate of 938 ml per day. Lastly, at 2,000 ml per day hydraulic loading, BOD reduction was 8.7 percent and production rate of gas was 164 ml per day. In spite of the low BOD treatment removal exhibited by the anaerobic filter process, its non-dependence on oxygen, the small amount of sludge produced and its conversion of organic matter basically carbon dioxide and methane make the anaerobic filter process a worthwhile low-cost alternative to be considered in wastewater treatment.